Upaya Meningkatkan Hasil Belajar Tentang Tekanan Melalui Model Pembelajaran Student Team Achievment Division (STAD) pada Siswa Kelas VIII A SMP Negeri 11 Kota Serang SMP Negeri 11 Kota Serang - humaeroh humaeroh; Sulastri Sulastri; Uyun Yuningsih; Lita Febriyani (Journal on Education, 2023)
This study aims to determine the efforts of teacher application in improving student learning outcomes in biology learning; and want to prove that the student team achievment division (STAD) learning model can improve learning outcomes on the concept of the digestive system in humans. This study uses Classroom Action Research (PTK) with a qualitative descriptive type. Through this study, the author seeks to take the steps of data collection, classification, data analysis, making conclusions with the aim of making an objective picture of a situation. The results showed that in the learning process so that students can interact and cooperate between students, the formation of small groups is very suitable for the development of grade VIII.4 students; Furthermore, to improve Biology learning outcomes, teachers can use several special learning models for grade VIII.4 SMP Negeri 11 Kota Serang with a cooperative approach of the student team achievment division (STAD) type.